A band-to-band transition visible-light-responsive anatase titania photocatalyst by N, F-codoping for water splitting and CO2 reduction. Issue 1 (7th December 2022) - Lian, Juhong; Shibata, Kengo; Xiao, Yejun; Du, Shiwen; Tanaka, Toshiya; Qi, Yu; Ishitani, Osamu; Maeda, Kazuhiko; Feng, Zhaochi; Zhang, Fuxiang
Abstract : A band-to-band transition visible-light-responsive N, F-codoped anatase TiO2 photocatalyst with low Ti 3+ defects is prepared for water oxidation/reduction, CO2 reduction and Z-scheme overall water splitting under visible-light irradiation. Abstract : To efficiently utilize solar energy and catalyze the water splitting reaction under visible-light, a novel strategy of first nitridation and subsequent calcination post-treatment methods is developed to prepare N, F-codoped TiO2 (TNOF) photocatalysts in this work. The prepared sample exhibits obvious band-to-band absorption with an edge up to ca. 580 nm. After calcinating the nitrided sample at low temperature in air, the Ti 3+ defects, which could trap photo-generated electrons during photocatalysis, would be significantly reduced. Under visible-light irradiation, the TNOF photocatalyst presents excellent water oxidation performance in AgNO3 aqueous solution or Fe 3+ reversible electron acceptor. Based on the obtained TNOF sample, an efficient Z-scheme water overall splitting system is successfully constructed combining with a known Ru/SrTiO3 :Rh H2 -evolution photocatalyst. Moreover, the TNOF photocatalysts also show good visible-light-driven water reduction and CO2 reduction activities. This work presents a novel strategy to prepare nitrogen-incorporated oxide photocatalysts with low defect concentrations for photocatalytic applications.